Oxidative and histological variations of LDLR -/- female mice ovaries submitted to different diets (Research, Society and Development, 2022)
Objective: to evaluate the oxidative and histological variations of female mice’s ovaries submitted to different diets. Methodology: Wild female mice (C57BL6) and LDLR-/- were used. They were divided into 4 groups (n=10): WTS: fed a standard diet; WTHL: fed a high fat diet; KOS: LDLR-/-, fed a standard diet; KOHL: LDLR-/-, received a high fat diet. After 60 days, blood was collected in order to verify of plasma glucose and insulin levels, the HOMAir was updated and serum lipid level were measured. After euthanasia, the ovaries were collected, weighed, freshly examined, one ovary was sent for histological preparation and the other was sent for preparation for oxidative stress assessment. Results: The ingestion of high-fat diet caused hypercholesterolemia, both the KOHL and WTHL groups, when compared to their respective control groups. In the KOHL group, severe hypercholesterolemia caused insulin resistance, verified by the increase in HOMAir. Dietary and genetic hypercholesterolemia associated with insulin resistance, verified in the KOHL, group increased lipoperoxidation and ovarian protein oxidation. No group had ovarian anatomical alterations or differences between the numbers of follicles and corpora lutea. Conclusion: the association between genetic and dietary dyslipidemia caused ovarian oxidative stress and insulin resistance in the ovaries, but didn’t cause morphological and histological changes to the ovaries of mice.